(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
Teacher professionalization is provided in the initial and continuous training that teachers participate throughout their professional trajectories. The main perspectives for which formation happen are named technical-specialist and practice, which are characterized, respectively, by the instrumental application of a set of knowledge, seeking to solve a problem, and by reflexivity. Thus, the objective was to analyze whether the technical-specialist and practical perspectives are evidenced in the teachers’ conceptions, about science teaching, scientific knowledge, teacher’s role, and curriculum, and how this happens. There were 5 post-graduate teachers in the area of Science and Mathematics Teaching, who answered a questionnaire with open questions, which was analyzed in a qualitative way, serving as a basis for propositions. Answers that could be related to the technical-specialist perspective appeared in some questions, which suggests that the formation of the concepts was based on an insufficient reflexive model of formation. On the other hand, in others, there was recognition of the role of reflexivity in teaching and learning, demonstrating a practical perspective. These results indicate the need to prioritize the formation of reflective teachers, whose identities are not based on the accumulation of contents, or the reproduction of methods and techniques.